TF2AngleNet: Continuous finger joint angle estimation based on multidimensional time–frequency features of sEMG signals - Jiang, Hai; Yamanoi, Yusuke; Chen, Peiji; Wang, Xin; Chen, Shixiong; Yong, Xu; Li, Guanglin; Yokoi, Hiroshi; Jing, Xiaobei (Biomedical signal processing and control, 2025)
Current pattern recognition-based myoelectric prosthetic hand control methods map electromyography (EMG) signals to specific hand postures, achieving high accuracy but often resulting in unnatural movements during transitions, reducing the hand’s anthropomorphic nature. While some studies predict single-finger joint angles from EMG signals, these approaches lack practicality since arm muscles often control multiple fingers simultaneously. This study proposed a TF2AngleNet that predicts six finger joint angles using both time domain raw signals and frequency domain features of EMG signals. A novel non-contact joint angle measurement method was used to collect EMG and joint angle data from five healthy subjects over five days. The experimental results demonstrate that TF2AngleNet achieves outstanding performance in continuous joint angle estimation, with a correlation coefficient of 94.7%, an R2 value of 89.2%, and an NRMSE of 9.5%. Notably, this represents a 12.43% improvement in NRMSE, along with average gains of 1.2% in CC and 2.42% in R2 compared to single-domain models (p-values < 0.05 across all metrics). Also, hand postures were shown using a virtual hand model, providing a natural and bionic control method of myoelectric hands. Additionally, a novel conceptual framework is proposed to reduce barriers to using pattern recognition-based prosthetic hands, with this study serving as its first stage by validating the model’s performance under three experimental conditions. This research provides a promising solution for dexterous, biomimetic and practical myoelectric prosthetic hand control methods. [Display omitted] •Developed a method for continuous finger joint angle estimation using muscle signals.•Multi-dimension time-frequency features are used to achieve high accuracy.•Created a non-contact finger motion measurement system, replacing data gloves.